Use of Information Technology Media on Physical Activities of Students - Suryansah; Hariadi; Suryadi, Lalu Erpan (Journal of physics. Conference series, 2020)
Where physical activity is very important for the health of every human being in carrying out daily activities as well as unexpected activities. Activities that are less mobile due to too often playing the virtual world such as online and offline games, internet, watching television too much will lead to the risk of obesity / obesity. Overweight / obesity is considered as a frightening specter and risk factors for various diseases, such as heart disease, hypertension and many others. One effort that is considered to reduce the risk of obesity is to increase physical activity. Physical activity is not only limited to special sports activities, but also other activities that require physical work, such as cleaning the house, sweeping, mopping, washing, walking, dancing, painting, hoeing, walking and so on. This study aims to determine whether there is an influence and how much information technology users on the physical activity of students of SMAN 1 Mantang. This research is a non-experimental research. The subjects in this study were students of class X SMAN 1 Mantang by using cluster random sampling consisting of 5 classes with a total poulasi of 141 students / students categorized as 69 male students and 72 female students. And from the cluster random sampling results obtained 5 classes with a total sample of 100 students. From the results of statistical calculations, it can be concluded that there is no significant effect between the use of information technology on students' physical activities. Because the data testing carried out shows that r count is smaller than r count table (-.717)> r table (0.197).